2017
DOI: 10.1093/isq/sqw051
|View full text |Cite
|
Sign up to set email alerts
|

The Tortuga Disease: The Perverse Effects of Illicit Foreign Capital

Abstract: Transnational crime brings substantial foreign capital into a number of fragile and developing states. Yet the economic and political impacts of such capital have rarely been studied due to the challenges of obtaining accurate data on illicit activities. We overcome this challenge by compiling a dataset on the amount and disbursement dates of ransom payments made by ship owners and insurers to Somali pirates from 2005 to 2012, along with sub-national commodity prices and trade flows in Somalia. Using a differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…Shortland (2012) investigated how satellite-based measures of economic growth show that geographic areas connected to Somali pirate groups see improvements in local economic conditions. Similarly, Oliver, Jablonski, and Hastings (2017) investigated how ransom disbursements coincide with changes in commodity prices in areas of Somalia associated with piracy.…”
Section: Illegal Capital Flight and Money Launderingmentioning
confidence: 99%
“…Shortland (2012) investigated how satellite-based measures of economic growth show that geographic areas connected to Somali pirate groups see improvements in local economic conditions. Similarly, Oliver, Jablonski, and Hastings (2017) investigated how ransom disbursements coincide with changes in commodity prices in areas of Somalia associated with piracy.…”
Section: Illegal Capital Flight and Money Launderingmentioning
confidence: 99%
“…8 Majid (2010: p. 11) reported that the northern Somali livestock trade involves the export of more than US$200 million worth of live animals across the Gulf of Aden each year. Livestock exports through the port of Bosasso in Puntland alone brought in US$113 million in 2011 (Oliver et al, 2014).…”
Section: The Livestock Tradementioning
confidence: 99%
“… 13. Oliver et al (2014) suggested yet another channel by which Somali piracy hurts the Somali economy. They estimated that ransom earnings from Somali piracy had the effect of appreciating the local currency and reducing export competitiveness. …”
mentioning
confidence: 99%
“…In fact, recent analysis has argued that the injection of ransom money from piracy hijackings into Puntland's economy actually led to Dutch Disease-like symptoms, with inflation in the prices of consumables, and a relative decrease in productive exports like cattle (notably, Puntland exports of cattle stayed relatively flat across the whole time period, while Somaliland exports increased from 2009 onward) (Oliver et al . 2017). Thus, any deficiencies in Puntland's economy relative to Somaliland's may have been caused by the rise of piracy, not the other way around.…”
Section: Comparing Puntland and Somalilandmentioning
confidence: 99%
“… 6. The data are derived from International Maritime Organisation statistics and the dataset used in Oliver et al (2017). We restricted attacks to successful attacks that appeared to be kidnappings for ransom originating from Somalia, with success defined as the pirates successfully boarding the ship, rather than successfully hijacking it or actually receiving a ransom.…”
Section: Notesmentioning
confidence: 99%